Bacterial Diversity and Population Dynamics During the Fermentation of Palm Wine From Guerrero Mexico - Astudillo-Melgar, Fernando; Ochoa-Leyva, Adrián; Utrilla, José; Huerta-Beristain, Gerardo (Frontiers in Microbiology, 2019)
Palm wine is obtained by fermentation of palm tree sap. In the Pacific coast of Mexico, palm wine is called Tuba and it is consumed as a traditional fermented beverage. Tuba has empirical applications such as an auxiliary in gastrointestinal diseases and a good source of nutrients. In the present study, a next-generation sequencing of the V3-V4 regions of the 16S rRNA gene was employed to analyze bacterial diversity and population dynamics during the fermentation process of Tuba, both in laboratory controlled conditions and in commercial samples from local vendors. Taxonomic identification showed that Fructobacillus was the main genus in all the samples, following by Leuconostoc, Gluconacetobacter, Sphingomonas, and Vibrio. Alpha diversity analysis demonstrated variability between all the samples. Beta diversity clustered the bacterial population according to the collection origin of the sample. Metabolic functional profile inference showed that the members of the bacterial communities may present the vitamin, antibiotic and antioxidant biosynthesis genes. Additionally, we further investigated the correlation between the predominant genera and some composition parameters of this beverage. This study provides the basis of the bacterial community composition and functionality of the fermented beverage